2002
DOI: 10.1097/00000539-200203000-00038
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Neuromuscular Block After Rocuronium In Postpartum Patients

Abstract: Neuromuscular block is prolonged in the postpartum period after standard doses of rocuronium. Drug administration according to lean body mass will produce a more consistent duration of block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…It is known that aminosteroid muscle relaxants can have a longer duration of action in immediately postpartum patients, 21 probably due to relative hepatic hypoperfusion in pregnancy as well as increased protein binding and competition with steroidal hormones for hepatic binding sites 16,22 . Concern over this prolonged duration of action means that there is a tendency to use the lower dose of rocuronium 0.6 mg/kg for RSI in pregnancy, despite a rate of poor or inadequate intubating conditions unless higher doses of an induction agent are used 11 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that aminosteroid muscle relaxants can have a longer duration of action in immediately postpartum patients, 21 probably due to relative hepatic hypoperfusion in pregnancy as well as increased protein binding and competition with steroidal hormones for hepatic binding sites 16,22 . Concern over this prolonged duration of action means that there is a tendency to use the lower dose of rocuronium 0.6 mg/kg for RSI in pregnancy, despite a rate of poor or inadequate intubating conditions unless higher doses of an induction agent are used 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Physiological and pathological changes occur during pregnancy, leading to pharmacological changes [ 106 ]. However, there were no differences in the onset times of non-depolarizing neuromuscular blocking agents in a comparison of women who were not pregnant and women immediately after giving birth [ 107 ].…”
Section: Coexisting Diseasementioning
confidence: 99%
“…Prolonged neuromuscular block has also been described with sevoflurane for maintenance of anaesthesia. 16 We used the facial nerve to monitor neuromuscular blockade and at the end of surgery our patient received 0.07 mg/kg neostigmine rather than the recommended dose of 0.05 mg/kg. Although it has been shown that cirrhotic patients have a 28% reduction in clearance and 55% increase in the elimination half life of rocuronium, 14 our patient's transaminases were only slightly raised and we felt that this was not a major factor in her prolonged neuromuscular blockade.…”
Section: Discussionmentioning
confidence: 99%